Influence of store atmosphere price and service quality on consumer loyalty of Mie Gacoan Cikarang - Wida Nurhaliza; Primaraga Sumantri Indra Wicaksana (Enrichment : Journal of Management, 2023)
Business people certainly expect loyalty from their customers to the business they have. Convenience when carrying out activities in the store, be it for eating, shopping, or interacting, is a consideration for consumers to choose where they want to spend their time. Another aspect that is considered by consumers to make repeat transactions is cheap and affordable prices. The better the quality of service, the higher customer satisfaction will be achieved, which means that profits will also increase. This research uses Quantitative method. The measurement method used in this study is Accidental Sampling where the sample to be taken is 100 respondents. The data collection method is to conduct a literature study by collecting journal articles and books that are relevant to this research. In addition, it also provides a list of questions (questionnaire) related to the observed variables. The data analysis method in this study used statistical tools, namely SPSS software version 25 and Microsoft Excel 2016. The results of this study indicate that store atmosphere has a partial effect on consumer loyalty with evidence that the t-count X1 is -0.068 <1.984 and the sign value is 0.946>0.05. Price has a partial effect on consumer loyalty with evidence that the t-count X2 is 2.291> 1.984 and the sign value is 0.024 <0.05. Service quality has a partial effect on customer loyalty with evidence that the t-count X3 is 7.366> 1.984 and the sign value is 0.00 <0.05.